Upaya Guru PPKn dalam Mengembangkan Civic Knowledge Melalui Gerakan Literasi Budaya dan Kewargaan - Martina, Lili (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
The inadequate reading proficiency, skill, and interest among students have been linked to a deficiency in their civic knowledge. This circumstance is notably evident at SMAN 7 Padang. This study addresses this concern by employing qualitative research methods. Data collection involved observation, interviews, and documentation techniques, while analysis comprised data reduction, presentation, and verification. The findings highlight that enhancing civic knowledge among students at SMAN 7 Padang can be achieved through specific measures: 1) adopting problem-based learning in civic education, 2) hosting quiz competitions focusing on the four pillars of nationality, 3) fostering a culture of literacy, and 4) leveraging the resources available in school libraries. Challenges faced by civic education teachers include student diversity, limited time allocation, and suboptimal classroom management. Notably, this research primarily explores internal school strategies for implementing civic knowledge, acknowledging the need for further research to delve into the impact of extracurricular activities on this endeavor.